Behavioral Profile in RASopathies. Issue 4 (23rd January 2014) - Alfieri, Paolo; Piccini, Giorgia; Caciolo, Cristina; Perrino, Francesca; Gambardella, Maria Luigia; Mallardi, Maria; Cesarini, Laura; Leoni, Chiara; Leone, Daniela; Fossati, Chiara; Selicorni, Angelo; Digilio, Maria Cristina; et al.
<x xml:space="preserve">Abstract</x> Here, we describe neurobehavioral features in patients with RASopathies (i.e., Noonan syndrome, LEOPARD syndrome, Costello syndrome, and cardiofaciocutaneous syndrome), developmental disorders caused by mutations in genes coding transducers participating in the RAS‐MAPK signaling cascade. Parents of 70 individuals with a RASopathy were asked to fill out the following questionnaires: Child Behavior Checklist (CBCL), Social Communication Questionnaire version lifetime (SCQ‐L), and Modified Checklist for Autism in toddlers (M‐CHAT). Data analysis indicated high rates of internalizing (37%) and externalizing problems (31%) on CBCL. Scores over the cut‐off were documented in 64% of patients with cardiofaciocutaneous syndrome, 44% with Costello syndrome, and 12% with Noonan syndrome on SCQ‐L/M‐CHAT. Our findings indicate that mutations promoting dysregulation of the RAS‐MAPK cascade mark an increased psychopathological risk and highlight that autistic‐like behavior could be underdiagnosed in patients with RASopathies. © 2014 Wiley Periodicals, Inc.